Tata Cara Penyusunan Rencana Pembangunan Daerah Kabupaten/Kota di Aceh - Eddy Purnama (Universitas Syiah Kuala, 2013)
ABSTRACT: In accordance to the Law Number 25, 2004 on National Development Planning System, regional development is one of the subsystems of such National System. Therefore, regional development must be able to accommodate two important needs, namely superior government and local community needs. In order to get legal certainty in fulfilling the important needs, it is significant to know a juridical basis that can be used as legal protection in deciding regional development planning system, which is conducive to demand aspiration of community and certain laws. It is found that the basis of regional/municipal developments in Aceh province is in accordance to the Law Number 11, 2006 on Aceh Government in relation to the Law Number 25, 2004 on National Development Planning System which has given autority to regional/municipal governments in order to design their regional development planning system by Qanun. Considering the needs, regional or municipal government must follow the rules that stated in the Minister of Internal Affairs’s Regulation Number 54, 2010 on Implementation of the Government Regulation Number 8, 2008 on Staging, Compiling System, Controlling, and Evaluation of Regional Development Planning Implementation. The Procedure Of Districts And Municipalities Development Planning In Aceh